FIGURE 12 in Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930 - Ermilov, Sergey G.; Makarova, Olga L.; Behan-Pelletier, Valerie M. (Zenodo, 2022)
FIGURE 12. Map on distribution of Oromurcia spp. compiled from published data (Thor 1930; Willmann 1939; Hammer 1944, 1946; Dalenius 1960; Karppinen & Krivolutsky 1982; Golosova et al. 1983; Karppinen et al. 1987; Seniczak & Solhøy 1987; Karppinen et al. 1992; Starý 1993a, b, 1996, 2005, 2006a, b; Luxton 1996; Gjelstrup & Solhøy 1994; Krivolutsky et al. 1995; Skubała & Gulvik 2005; Seniczak et al. 2006; Gabris et al. 2008; Mahunka & Mahunka-Rapp 2008; Hågvar et al. 2009; Melamud 2009; Heggen 2010; Shtanchaeva & Subías 2010; Mahunka et al. 2013; Makarova & Behan-Pelletier 2015; Weigmann et al. 2015; Schatz 2020), and four original finds—two from Greenland as well as records from Kola Peninsula and Kolguev Island. Red circles—Oromurcia bicuspidata, blue circles—Oromurcia sudetica, asterisk—Oromurcia magadanensis sp. nov. Published as part of Ermilov, Sergey G., Makarova, Olga L. & Behan-Pelletier, Valerie M., 2022, Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930, pp. 30-52 in Zootaxa 5187 (1) on page 48, DOI:10.11646/zootaxa.5187.1.5, http://zenodo.org/record/7078260